CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE , RETURN ON EQUITY DAN NILAI PERUSAHAAN - MOHAMAD ADAM; H M A RASYID HS; ELGA RISZKY MAULIDYNA ANIS (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2014)
This research aims to know: (1) The influence of Corporate Social Responsibility (CSR) Disclosure partially on firm value (2) The influence of Return on Equity (ROE) partially on firm value (3) The influence of Corporate Social Responsibility (CSR) Disclosure and Return on Equity (ROE) simultaneously on firm value. The population of this research are the winners of 7th Indonesia Sustainability Reporting Award (ISRA) and 8th Indonesia Sustainability Reporting Award (ISRA). The sampling technique that used for this research is purposive sampling. Total number of sample are taken from 9 firms with 4 years research period which was from 2009 to 2012. The analysis of data uses multiplied regression. The result of this research shows that: (1) Partially, the Corporate Social Responsibility (CSR) Disclosure has not significant effect to firm value (2) Partially, Return on Equity (ROE) has significant effect to firm value (3) Simultaneously, Corporate Social Responsibility (CSR) Disclosure and Return on Equity (ROE) has significant effect to firm value. Â